(untitled) (Revista Brasileira de Contabilidade e Gestão, 2023)
The main article objective is to analyze the incubators of technology-based companies and present their characteristics. They were mapped 84university incubators located in Brazil and analyzed only 44 called themselves as technology-based incubators. Therefore, one sees a pattern of actions, infrastructure, incubation processes and selection of technology-based incubators. All have the characteristics of use of these infrastructures in universities, alignment of technical, economic and market requirements as to the selections for companies for entering the incubation process and the average time of 24 months in the whole process.